2016
DOI: 10.1371/journal.pone.0152217
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Levels and Domains Assessed by Accelerometry in German Adolescents from GINIplus and LISAplus

Abstract: BackgroundPhysical activity (PA) is a well-known and underused protective factor for numerous health outcomes, and interventions are hampered by lack of objective data. We combined accelerometers with diaries to estimate the contributions to total activity from different domains throughout the day and week in adolescents.MethodsAccelerometric and diary data from 1403 adolescents (45% male, mean age 15.6 ± 0.5 years) were combined to evaluate daily levels and domains of sedentary, light, and moderate-to-vigorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 37 publications
5
53
0
3
Order By: Relevance
“…Tem sido demonstrado que rapazes são mais ativos que moças em diversos contextos da atividade física 24,25 . Similar ao verificado neste estudo, moças nigerianas também foram menos ativas no deslocamento que rapazes, mas não apenas nesse domínio, elas também foram menos ativas para atividade física no lazer e total 24 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Tem sido demonstrado que rapazes são mais ativos que moças em diversos contextos da atividade física 24,25 . Similar ao verificado neste estudo, moças nigerianas também foram menos ativas no deslocamento que rapazes, mas não apenas nesse domínio, elas também foram menos ativas para atividade física no lazer e total 24 .…”
Section: Discussionunclassified
“…Similar ao verificado neste estudo, moças nigerianas também foram menos ativas no deslocamento que rapazes, mas não apenas nesse domínio, elas também foram menos ativas para atividade física no lazer e total 24 . Resultado similar foi identificado em estudo com adolescentes alemães para padrões de atividade física, por domínio, utilizando-se de acelerometria 25 . No entanto, diferenças entre sexos para o tipo de deslocamento mais prevalente em jovens não é consenso na literatura nacional [10][11][12] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…This study used data from the 15‐year follow‐up of two birth cohorts: GINIplus and LISAplus. Methodological details on both studies are available at the study websites and published elsewhere (von Berg et al ., ; Chen et al ., ; Smith et al ., ,b). Briefly, 7642 healthy full‐term infants (52% male) were recruited at birth in the German cities of Munich and Wesel between 1995 and 1999.…”
Section: Methodsmentioning
confidence: 99%
“…These 1411 (46% male) are the subjects of the current study. Previous research (Smith et al ., ,b) showed that at each stage of follow‐up subjects were more likely to be female and urban (from Munich rather than Wesel), and less exposed to pre‐ and postnatal tobacco than the cohorts from which they were drawn.…”
Section: Methodsmentioning
confidence: 99%